A construção "cortei o cabelo" em português - Isabella Amarante Maciel (2024)
This dissertation presents a study on a special use of the transitive construction with an extended meaning, illustrated by 'cortei o cabelo' (I cut my hair). In Brazilian Portuguese (BP), language users employ a familiar form, the transitive [SN V SN], to convey a meaning different from the prototypical senses, as in 'cortar o bolo', or from the more common extended ones, as in events described by verbs such as 'amar'. In this special extended sense, the participant in the subject position is not the direct agent of the event but rather the one who requests a service, consents to its execution, and obtains it, within a conventionalized scenario of service provision (Maciel; et al 2022). Given the specialty of the construction, the following questions arise: i) how do language users extend the use of the transitive construction for the special meaning of 'cortei o cabelo'?; ii) why do they use the transitive structure to convey this special meaning?; and iii) what function is associated with the construction 'cortei o cabelo' and, consequently, what properties does it exhibit? As a hypothesis, the use of the construction 'cortei o cabelo' is motivated by its function, which explains all the properties and the distribution of the construction in the language. The main purpose of this study is to understand the use of this construction in the language in light of the theoretical assumptions of Usage-Based Linguistics, Cognitive Linguistics, and Goldberg's Construction Grammar. Specifically, this research: i) explains how speakers extend the prototypical meaning of the transitive construction to the special meaning of 'cortei o cabelo' and why they use the transitive form; ii) analyzes data to describe the functional aspects of the construction 'cortei o cabelo'; and iii) demonstrates how the function explains the properties of the construction 'cortei o cabelo'. To achieve the proposed objectives, it was necessary to collect data from Corpus do Português: NOW (2012-2019), in order to analyze the different uses and registers of the construction 'cortei o cabelo', considering the linguistic production of BP users. Additionally, a survey was administered to native speakers of BP to confirm the meaning attributed to the construction and to verify the awareness that language users have of the special meaning of the transitive construction. From the analysis of the data, it was possible to conclude that the conventional scenario of service provision is crucial for the special meaning of the construction 'cortei o cabelo', and all its characteristics can be understood in terms of its purpose: to report that a service was obtained, implying that something more was done. Its transitive form is motivated by its function, and the language users use this structure because it is a strong and accessible cluster, being more susceptible to extension of use.